PF-05231023 reduces lipid deposition in apolipoprotein E-deficient mice by inhibiting the expression of lipid synthesis genes - Zhao, Juan; Liu, Xuelong; Yue, Jingyu; Zhang, Shouquan; Li, Li; Wei, Hengxi (Frontiers in Veterinary Science, 2024)
Fibroblast growth factor 21 (FGF21) is a peptide hormone that is primarily expressed and secreted by the liver. The hormone is crucial for regulation of glucose homeostasis, lipid metabolism, and energy balance. Compared with natural FGF21, FGF21 analogs have become drug candidates for the treatment of cardio-vascular and metabolic diseases owing to their long half-life and greater stability in vitro. Apolipoprotein E (Apoe)-knockout (Apoe-/-) mice exhibit progressive disruptions in lipid metabolism in vivo and develop further atherosclerosis pathological features owing to Apoe deletion. Therefore, this study used an Apoe-/- mouse model to investigate the effects of a long-acting FGF21 analog (PF-05231023) on lipid metabolism and related parameters. Eighteen Apoe-/- female mice were fed a Western diet equivalent for 12 weeks, and then randomly assigned to intraperitoneally receive either physiological saline (the control group) or 10 mg/kg PF-05231023 (the treatment group) three times a week for seven consecutive weeks. Body composi-tion, glucose tolerance, blood and liver cholesterol, triglyceride levels, liver vacuolization levels, pe-ri-ovarian white adipocyte hypertrophy, aortic atherosclerotic plaque formation, and the expression of genes related to lipid metabolism in adipose tissue were subsequently assessed before and after treatment. The aortic atherosclerotic plaque area was reduced in mice in the PF-05231023 treatment group compared with that in the saline group. Although the effect of PF-05231023 on the plasma biochemical indexes of mice was small, it significantly reduced lipid levels and lipid droplet accumulation in the liver, and reduced adi-pocyte hypertrophy in white adipose tissue. Transcriptome analysis of adipose tissue showed that PF-05231023 treatment downregulated the expression of lipid synthesis-related genes and inhibited the sterol regulatory element binding transcription factor 1 gene, thereby improving lipid deposition. PF-05231023 effectively improved the lipid metabolism of Apoe-/- mice, demonstrating an an-ti-atherosclerotic effect and providing a scientific basis and experimental foundation for the clinical treat-ment of cardiovascular diseases by using long-acting FGF21 analogs.